Modular design for machine tools - Ito, Y. (Yoshimi), 1940- (McGraw-Hill, 2008)
Presents the information you need on modular design. This guide helps you to design and build machines using modular design methods. It helps you to shorten machine design time, improve reliability, and simplify service and repairs.